Association of brain-derived neurotrophic factor (Val66Met) genetic polymorphism with methamphetamine dependence in a Malaysian population - Sim, M.S.; Mohamed, Zahurin; Hatim, A.; Rajagopal, V.L.; Habil, M.H. (Elsevier, 2010)
Methamphetamine is a highly addictive psychostimulant that has surged in popularity worldwide in the last decade. Brain-derived neurotrophic factor (BDNF), a member of the neurotrophic factor family, is widely expressed in the adult mammalian brain and plays an important role in the long-term survival, differentiation, and outgrowth of neurons. Previous studies suggested that the BDNF gene may be involved in the mechanisms underlying substance dependence. This study investigated the association of the BDNF gene Val66Met polymorphism with methamphetamine dependence and with psychosis in a Malaysian population with different ethnicities. The BDNF Val66Met polymorphism was genotyped by PCR-RFLP in 186 male methamphetamine-dependent subjects and in 154 male controls of four different ethnicities, namely, Malay, Chinese, Kadazan-Dusun, and Bajau. Our results showed that the distribution of the BDNF Val66Met genotype in Chinese subjects with methamphetamine dependence (OR = 2.6, p = 0.015) and methamphetamine psychosis (OR = 0.2, p = 0.034) were significant compared with controls. The frequency of the 66Val allele in methamphetamine-dependent subjects was higher than that in the control group, suggesting that the 66Val carriers are more susceptible to methamphetamine dependence. However, 66Val allele frequency in other ethnicities was not significantly different from the controls. The results of the study also showed that in the Chinese methamphetamine-dependent subjects, there was a difference in allele frequency when comparing those who developed psychosis and those who did not. Our findings suggest that the BDNF Val66Met polymorphism may contribute to methamphetamine dependence and psychosis in the Chinese population but not in other Malaysian ethnicities. Â© 2010 Elsevier B.V. All rights reserved.